Swarming Aqua Sperm Micromotors for Active Bacterial Biofilms Removal in Confined Spaces - Mayorga-Martinez, Carmen C; Zelenka, Jaroslav; Grmela, Jan; Michalkova, Hana; Ruml, Tomáš; Mareš, Jan; Pumera, Martin (Advanced science (Weinheim, Baden-Wurttemberg, Germany), 2021)
Microscale self-propelled robots show great promise in the biomedical field and are the focus of many researchers. These tiny devices, which move and navigate by themselves, are typically based on inorganic microstructures that are not biodegradable and potentially toxic, often using toxic fuels or elaborate external energy sources, which limits their real-world applications. One potential solution to these issues is to go back to nature. Here, the authors use high-speed Aqua Sperm micromotors obtained from North African catfish (Clarias gariepinus, B. 1822) to destroy bacterial biofilm. These Aqua Sperm micromotors use water-induced dynein ATPase catalyzed adenosine triphosphate (ATP) degradation as biocompatible fuel to trigger their fast speed and snake-like undulatory locomotion that facilitate biofilm destruction in less than one minute. This efficient biofilm destruction is due to the ultra-fast velocity as well as the head size of Aqua Sperm micromotors being similar to bacteria, which facilitates their entry to and navigation within the biofilm matrix. In addition, the authors demonstrate the real-world application of Aqua Sperm micromotors by destroying biofilms that had colonized medical and laboratory tubing. The implemented system extends the biomedical application of Aqua Sperm micromotors to include hybrid robots for fertilization or cargo tasks.
Keywords: spermbots; Equipment Contamination; Spermatocytes; Aqua Sperm micromotors; design vybavení; spermatocyty; Biofilms; Robotics; Biomimetics; biomimetika; Equipment Design; spermatozoa; sumci; mužské pohlaví; kontaminace zdravotnického vybavení; Animals; active bacterial biofilms; nanorobots; mikrotechnologie; Microtechnology; biofilmy; Male; biobots; robotika; zvířata; Catfishes